A High Gain Omnidirectional Antenna Using Negative Permeability Metamaterial - Hangfei Tang; Quanwen Hou; Yahong Liu; Xiaopeng Zhao (International Journal of Antennas and Propagation)
A high gain omnidirectional antenna with low profile is proposed and is investigated numerically and experimentally. Based on the conventional center-fed circular epsilon-negative (ENG) zeroth-order resonator (ZOR) antenna, dendritic structure negative permeability metamaterial (NPM) is used as the substrate to enhance the gain of the omnidirectional antenna. The experimental results show that the gain of a center-fed circular ENG ZOR antenna with NPM substrate is enhanced about 2.2 dB, and the efficiency is enhanced about 38%, in the whole broad operating bandwidth as compared to that of the antenna without NPM substrate, which can be used to improve the reliability of wireless communications.